Comparative analysis of automatic betta fish feeding devices based on IoT (Internet of Things) using Telegram bots - Cristo Maretus Seran (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Technology development in the That electronic industry own developed very fast recently. For push social entrepreneurship associated with using modern technology , A technology system For control fish food in the fish pool own has been built, planning to become implemented effectively And under control from a distance. That development information technology NO longer it seems to become only A complete, But A need. One example is technology in the That world from animal farm Which is develop quickly, offering farmers a variety of ways to manage their livestock more efficiently. Fish farming is A popular hobby in the Today public. Fish own A special attractiveness For fish lovers And demands in the That market continue to increase. That objective from This research is to develop an automatic fish feeding system based on NodeMCU ESP8266 and integrated with Telegram. Therefore, a microcontroller-based fish feeding device was developed. utility A NodeMCU ESP8266, And A drive/servo motor That Can move return And move on to open And close That feeding channel hole to take fish food from That fish feeding tube using Telegram application Which Can become under control from a distance. . Users Can monitor using Telegram robot with That available feature. Test results show That system potential to optimize food, allows remote control, And allows farmer to care For theirs fish more effective.